Genomic Analysis of Carbapenem-Resistant Pseudomonas aeruginosa Isolated From Urban Rivers Confirms Spread of Clone Sequence Type 277 Carrying Broad Resistome and Virulome Beyond the Hospital - Esposito, Fernanda; Cardoso, Brenda; Fontana, Herrison; Fuga, Bruna; Cardenas-Arias, Adriana; Moura, Quézia; Fuentes-Castillo, Danny; Lincopan, Nilton (Frontiers in Microbiology, 2021)
The dissemination of antibiotic-resistant priority pathogens beyond hospital settings is both a public health and an environmental problem. In this regard, high-risk clones exhibiting a multidrug-resistant (MDR) or extensively drug resistant (XDR) phenotype have shown rapid adaptation at the human-animal-environment interface. In this study, we report genomic data and the virulence potential of the carbapenemase, São Paulo metallo-β-lactamase (SPM-1)-producing Pseudomonas aeruginosa strains (Pa19 and Pa151) isolated from polluted urban rivers, in Brazil. Bioinformatic analysis revealed a wide resistome to clinically relevant antibiotics (carbapenems, aminoglycosides, fosfomycin, sulfonamides, phenicols, and fluoroquinolones), biocides (quaternary ammonium compounds) and heavy metals (copper), whereas the presence of exotoxin A, alginate, quorum sensing, type II, III and VI secretion systems, colicin, and pyocin encoding virulence genes was associated with a highly virulent behavior in the Galleria mellonella infection model. These results confirm the spread of healthcare-associated critical-priority P. aeruginosa belonging to the MDR sequence type 277 (ST277) clone beyond the hospital, highlighting that the presence of these pathogens in environmental water samples can have clinical implications for humans and other animals.